Theological Study of the Ethics of Artificial Intelligence (AI) Based on Legal Principles and Biblical Provisions: Perspectives for Christian Religious Education - Lucky Antonio; Donalia Reynaldo (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
This study examines the integration of Artificial Intelligence (AI) in Christian Religious Education (PAK), using four Biblical principles love, justice, truth, and stewardship as a framework. Employing a qualitative approach with thematic triangulation through interviews with leaders, lecturers, and students, the research aims to understand how AI can be used ethically in PAK. The findings indicate that AI, when applied thoughtfully and ethically, can significantly enhance the learning process. The principle of love emphasizes the importance of honesty, empathy, and a compassionate approach in the use of AI. Justice calls for equitable access to AI tools, ensuring that all learners can benefit regardless of their backgrounds. The principle of truth encourages theological discernment in the application of AI, ensuring that it aligns with Christian teachings. Stewardship highlights the responsibility to manage AI technologies wisely, using them to serve God's purposes. AI is viewed not as a replacement for human educators but as a tool to serve and glorify God in the educational process. The study suggests that theological institutions should create ethical AI guidelines to ensure responsible use and should focus on enhancing faith-based digital literacy among students, preparing them for the digital age while remaining rooted in their faith.